Dose Response of Total Saponins Isolated from the Stem Bark of Dialium Guineense - O.D., Abu; I.O., Onoagbe; I., Ojo (Journal of Advances in Plant Biology, 2022)
The safety of plant-derived bioactive compounds has become a global concern. The present study investigated the dose response of total saponins isolated from the stem bark of Dialiumguineense. Adultmale Wistar rats (n = 15) weighing 170 – 190 g (mean weight = 180 ± 10 g) were randomly assigned to three groups (5 rats per group). The rats received varied doses of total saponins isolated from the stem bark of the medicinal plant (50 - 150 mg/kg body weight, bwt) orally for a period of 9 days. The concentration of fasting blood glucose (FBG) was used as the therapeutic index.The results of the analysis revealed that total saponins isolated from the stem bark of D. guineense significantly reduced the Fasting Blood Glucose (FBG) levels of normal Wistar rats (p < 0.05). The graded and quantal dose-response curves showed that150 mg/kg bwt was effective in reducing the blood glucose of rats (produced the best hypoglycemic effect). The study concluded that total saponins isolated from the stem bark of D. guineense possesses hypoglycemic effect at a relatively good dose.
Keywords: Fasting blood glucose